PENGARUH TEKANAN KETAATAN, TEKANAN ANGGARAN WAKTU, KOMPLEKSITAS TUGAS, PENGETAHUAN DAN PENGALAMAN AUDITOR TERHADAP AUDIT JUDGMENT (Studi Empiris Pada Auditor Inspektorat Provinsi Riau) - Aulya Afri Yolanda; Yusralaini Yusralaini; Susilatri Susilatri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose that wish to be reached in this research is to test empirically and analyze variable obedience pressure, time budget pressure, task complexity, knowledge and experience which directly influence audit judgment. Data in this research were obtained from questionnaires (primary). Population in this research is Auditor’s at Inspektorat Riau Province. Data analysis conducted with multiple linear regression model with help of software SPSS version 20.0. The result of this research showed that variable obedience pressure doesn’t has effect to audit judgment. It comes from the probability significance that is 0.519. Time budget pressure has a significant effect to audit judgment. It comes from the probability significance that is 0.007. Task complexity has a significant effect to audit judgment. It comes from the probability significance that is 0.011. Knowledge has a significant effect to audit judgment. It comes from the probability significance that is 0.001. Experience has a significant effect to audit judgment. It comes from the probability significance that is 0.003. The conclusion can be made from the result that there is an effect of obedience pressure, time budget pressure, task complexity, knowledge and experience together to audit judgment. Obedience Pressure, Time Budget Pressure, Task Complexity, Knowledge and Experience has effect to Audit Judgment, indicated with the signification 0,000 and coefficient of determination (R 2 ) 0,619.Keywords : obedience pressure, time budget pressure, task complexity, knowledge, experience and audit judgment